(untitled) (Environment & Health, 2016)
The scientific substantiations for the revision of existing Ukrainian sanitary norms SN № 34077-84 «Sanitary norms of allowable noise in residential and public buildings and in residential areas" and DBN V.1.1-31: 2013 «Protecting areas of houses and buildings from the noise. Materials and methods. An analysis of the literature on the evaluation criteria of noise in residential and public buildings. Calculation of the corrected scale "A" sound levels - DSTU-NB V.1.1-35: 2013 "Guidelines for the calculation of noise levels in the rooms and in the territories" Appendix B. Calculation of SIL - by ANSI S12.2-2008: “Criteria for Evaluating Room Noise”. Calculation of the required reduction and the required insulation - by DBN V.1.1-31: 2013. “Protecting areas of houses and buildings from the noise”. Results. The inconsistency in CH № 3077-84 and DBN V.1.1-31: 2013 according of permissible sound pressure level to its permissible sound levels was proved, which leads to incorrect hygienic assessment of noise in the rooms and in the territories. It was proved that the use of permissible sound pressure levels CH № 3077-84 and DBN V.1.1-31: 2013, the calculation of the required sound insulation of building envelopes leads to an underestimation of its values, which in turn leads to disruption of the acoustic mode planned residential premises and public buildings is still at the design stage. Recommended permissible sound levels and sound pressure for residential and public buildings. Conclusions. The scientific basis for the revision of existing Ukrainian sanitary norms SN № 34077-84 «Sanitary norms of allowable noise in residential and public buildings and in residential areas" and DBN V.1.1-31: 2013 “Protecting areas of houses and buildings from the noise”.